PERAN ORANG TUA DALAM PENERIMAAN DIRI REMAJA PENYANDANG CACAT FISIK DI NAGARI AIR BANGIS KECAMATAN SUNGAI BEREMAS KABUPATEN PASAMAN BARAT - Sadli, Rafiqal; Kasih, Fitria; Zulkfli, Zulkfli (Bimbingan dan Konseling, 2013)
This research was motivated by parentsâ roles in receiving of physically disabled adolescent. This research focuses on: (1) Parentsâ role in the social adjustment of adolescents with physical disabilities, (2) Parentsâ role in self- concept development of adolescents with physical disabilities. This research was a descriptive qualitative research. The sample was taken by using snowball sampling technique. This research took the parents of teenagers with physical disabilities as key informants. Additional informants were physically disabled adolescents and adolescents with physical disabilities neighbors. Based on the results of research on parentsâ role in adolescent social adjustment with physical disabilities, in which the parents have a role in giving attention, motivation, attention of sadness feelings, complain, and bring teens to seek the treatment, meanwhile motivational support in the form of a spirit not to be shy and accept who she/he is. Parentsâ role in the development of self-concept look of a parenting parents teach children gratitude, freedom does not prohibit children to play, giving their needs, while support in the form of the spirit do not despair, acceptance is shown by giving attention to youth, the intimacy of the relationship and communication is established with good.Â